Ultra-violet health monitoring of smart composite laminate using embedded fiber Bragg grating sensors. (September 2020) - Mohanta, S; Padarthi, Y; Chokkapu, S; Gupta, J; Neogi, S
A novel approach is developed to evaluate the property retention on prolonged ultra-violet exposure and hence, health monitoring of glass fiber reinforced polymer composite laminate. This is achieved in a non-destructive manner by mapping the strength retention with the established strain. Embedded fiber Bragg grating sensor and strain gauges are employed to monitor the strain evolution within the laminate. Tensile and flexural tests are conducted at regular intervals to estimate the mechanical strength retention with varying duration of ultra-violet exposure. Through this analysis, it is observed that the property degradation mechanism follows the first-order reaction kinetics. The degradation of matrix material along with the stress relaxation over time develops the stress–strain fields near the interfaces of matrix and fiber. Moreover, the established strain is interpreted by formulating the model that considers the unifying influence of stress relaxation and chemical degradation. This model has closely (R 2  = 0.9810 and 0.9790) predicted the experimental data of strain than the existing ones (R 2  = 0.9142 and 0.9119). Besides, property retention is mapped with the predicted strain. More importantly, FESEM and FTIR confirm the fact that ultra-violet radiation degrades the matrix material, and thus the mechanical property gets significantly deteriorated. This suggests that the strain measurement is an effective, non-destructive and health monitoring technique to assess the property degradation of the manufactured glass fiber reinforced polymer composites.